2018
DOI: 10.4028/www.scientific.net/kem.773.244
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Controlled Low Strength Material (CLSM) Made Entirely from By-Products

Abstract: Various by-products generated from thermal power plants and chemical industries have considerably economic and environmental impacts in South Korea. This study focuses on evaluating thermal conductivity of controlled low strength material (CLSM) made entirely from by-products (e.g., coal ash, gypsum, red mud). In the experimental program, pond ash is used as a full replacement of natural sand whereas fly ash activated by a little lime, red mud, and gypsum is the main binder in the production of CLSM. Various l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Due to considerations regarding material costs and environmental issues, the use of locally sourced aggregates for the preparation of flowable fly ash has gained widespread attention. Researchers such as Do et al [29] have studied the use of ponded ash (PA) and excavated soil (ES) as aggregates, and experimental results show that the compressive strength and fluidity of flowable fly ash decrease while the initial setting time lengthens with a decrease in the PA/ES ratio. Tuerkel [30] prepared flowable fly ash by adding limestone sand with particle sizes of 0-5 mm, and the results showed that as the limestone sand content increased, the water absorption of the flowable fly ash increased.…”
Section: Introductionmentioning
confidence: 99%
“…Due to considerations regarding material costs and environmental issues, the use of locally sourced aggregates for the preparation of flowable fly ash has gained widespread attention. Researchers such as Do et al [29] have studied the use of ponded ash (PA) and excavated soil (ES) as aggregates, and experimental results show that the compressive strength and fluidity of flowable fly ash decrease while the initial setting time lengthens with a decrease in the PA/ES ratio. Tuerkel [30] prepared flowable fly ash by adding limestone sand with particle sizes of 0-5 mm, and the results showed that as the limestone sand content increased, the water absorption of the flowable fly ash increased.…”
Section: Introductionmentioning
confidence: 99%
“…It is unanimously reported that the demand for portland cement and concrete, which are the most critical construction materials, has been significantly accelerating due to the global urbanization taking place over the world [1][2][3][4][5]. In 2021, 92 million metric tons of portland cement were produced in the U.S. and a total of 4.4 billion tons were manufactured worldwide [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers from several fields have investigated the development of CLSM utilizing by-product material [5,6,[9][10][11]. However, there is a lack of research focus on the incorporation of curing conditions on the strength of this material.…”
Section: Introductionmentioning
confidence: 99%